EVALUATION OF GENETIC DIVERGENCE IN INDIAN FLAX (LINUM USITATISSIMUM L.) - VIKAS PALI,; NANDAN MEHTA, (The Bioscan, 2015)
An experiment with fourty eight genotypes of flax carried out to study the nature and magnitude of divergence using Mahalanobis D 2 statistics, in randomized block design with three replication. The data for ten important quantitative traits recorded from the genotypes raised. The variability study indicated high to moderate phenotypic and genotypic coefficient of variation accompanied by high heritability and genetic advance as per cent of mean for traits, days to 50 per cent flowering, plant height and number of capsules per plant. The major character seed yield per plant possesses high heritability with high genetic advance, indicating their importance in selection for yield improvement. The 48 genotypes of flax were grouped into five clusters using Tocher’s method. Cluster IV comprising is the most divergent cluster.The genotypes in cluster III and cluster V, exhibited high degree of genetic diversity. Cluster III was suitable for seed yield per plant, number of capsules per plant, number of primary branches per plant and number of secondary branches per plant. Days to 50 per cent flowering and oil content contributed maximum towards genetic divergence.